Ronald Reagan's Strategies and Policies: Of Ideology, Pragmatism, Loyalties, and Management Style. Issue 4 (1st October 2016) - Dobson, Alan
ABSTRACT: This analysis interrogates how ideology, pragmatism, personal loyalties, and management style all contributed to policy and strategic decisions made by President Ronald Reagan and his Administration (1981–1989). This approach helps to clarify Reagan's achievements and shortcomings in what is still a somewhat conflicting historiography of his time as president. When woven together, generally, although not always, the three produced effective strategies for achieving clear objectives.